Front-end reactive architectures : explore the future of the front-end using reactive JavaScript frameworks and libraries - Mezzalira, Luca (Apress, 2018)
Learn how to use reactive architectures on the front end. There are many technologies using a reactive approach on the back end, but this book teaches you how the reactive manifesto can be used to benefit your front-end programming as well. You will discover what reactive programming is, what the current front-end ecosystem looks like, and how to use a range of frameworks and libraries. You will also apply specific reactive architectures in your own projects. Each concept is taught with a mix of technical explanations and real-world code implementations. The future of front-end programming and architecture is reactive - don't get left behind: Add Front-End Reactive Architectures to your library today. What You'll Learn Understand when and why you should use a reactive architecture Apply a specific reactive architecture in a project Manage different reactive architectures Who This Book Is For Mid-senior front end developers, tech leads, and solutions architects.